Efektivitas Pelaksanaan Pemberian Pendidikan Formal Bagi Anak-Anak Pengungsi Luar Negeri Di Kota Batam - Shahrullah, Rina Shahriyani; Susetyo, Heru; Sudirman, Lu; Sahputra, Rendi (Jurnal Hukum & Pembangunan, 2023)
The entire responsibility for all children in Indonesia lies with the government, and it extends to all children in Indonesia, not only those who are Indonesian nationals but also includes children who are refugees from foreign countries. One of the fundamental rights regulated by the laws and the Convention on the Rights of the Child ratified by Indonesia is the right to receive appropriate education (formal, non-formal, and informal education). This research aims to analyze the implementation of formal education fulfillment for refugee children in Batam City, especially those accommodated at Hotel Kolekta. Therefore, the research questions are as follows: 1) How effective is the fulfillment of the right to formal education for refugee children in Batam City? 2) What challenges do refugee children in Batam City face in obtaining the right to formal education? 3) What are the solutions for the fulfillment of the right to formal education for refugee children in Batam City? This research utilizes the empirical legal research method with a sociological approach, and it is analyzed qualitatively using the Effectiveness of Law Theory by Soerjono Soekanto as an analytical tool. The research findings indicate that the five factors in the theory are not yet effective due to legal factors related to specific technical implementation regulations for the fulfillment of the right to formal education for refugee children being absent. The ineffectiveness of law enforcement is due to the weak coordination among relevant parties, especially the Education Agency of Batam City, UNHCR, IOM, and schools in Batam. The facility factor is also ineffective due to the limited facilities in enhancing the Indonesian language skills of refugee children, resulting in a low interest in attending school and continuing formal education (Community Factor). Different cultures influence the social interaction of refugee children with the community of Batam City (Cultural Factor), causing a slow improvement in Indonesian language proficiency, which is the language of instruction in formal education in Batam City.